Development of a fermented milk dessert composition «Martyshka» - Dzyuba, Nadya; Valevskaya, Liudmyla; Atanasova, Vita; Sokolovskaya, Alena (Eastern-European Journal of Enterprise Technologies, 2017)
A recipe and technology for the production of a new fermented milk dessert Martyshka of increased nutritional value have been developed. The recipe of the new dessert includes such components (g/100 g): cottage cheese – 54, jam – 23, honey – 8, sesame – 4, cream – 6, and glutin – 5. The determined contents of the main food components (g/1 serving) are the following: proteins – 13.2, fats – 11.6, and carbohydrates – 46.3. The dessert is a source of vitamin C, and it covers 37.04 % of daily human needs. By introducing glutin into the dessert composition, the protein content of the finished product is increased, and it covers an average of 16.92 % of the daily requirement. Besides, the dessert is rich in calcium, so one portion of the dessert covers 25 % of the daily human need. The obtained data make it possible to claim that the developed dessert is the source of the main macro- and micronutrients, and it meets the demand for them at a high level. The research findings obtained during the evaluation of the microbiological and organoleptic indices during storage allow asserting that the new dessert «Martyshka» will be competitive on the consumer market of Ukraine. Thus, when the product is stored for 5 days at a temperature of (4±2) °C, the contents of coliform bacteria, Salmonella, mold fungi, yeast, and Staphylococcus aureus correspond to the sanitary and hygienic requirements for fermented milk desserts. The resulting dessert «Martyshka» can be recommended for children and as gerodietic nutrition.